The interface between research and policy-making in South Africa: exploring the institutional framework and practice of an uneasy relationship - Sven Grimm; Mareike Magdalena Gensch; Johanna Hauf; Julia Prenzel; Nitja Rehani; Sarah Senz; Olivier Vogel (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The interface between research and policy-making is gaining relevance, as global challenges and their complexities increase. Policy-makers worldwide discuss and need to address complex common global challenges such as climate change, peace and security or human food security. This is highly relevant to all countries, and comes with a particular urgency for globally engaging rising powers, of which South Africa is one. The aim of this paper is to explore the extent to which the South African science and policy systems facilitate or hinder research-based policy advice. This exploration starts with the policy institutions that shape science and academic research. Inter-institutional relations between government and research institutions, as well as funding and other, non-monetary, incentive structures are portrayed in order to assess their strengths and weaknesses. This research is empirically based on more than 100 interviews and background discussions conducted between February and April 2017 with South African and German actors, comprising university scholars from different universities and academic disciplines, researchers from think tanks, Non-Governmental Organisations (NGOs), and government agencies, as well as consultants, international actors and policy-makers. The interface between policy and research is tension-ridden in any context for a number of reasons, including, among other things, divergent rationales, different time-horizons and subsequently disappointed mutual expectations. Some tensions in the relationship between researchers and decision-makers, however, also emanate from the specific context in which the interface between researchers and decision-makers is organised. In order to address these tensions, the following recommendations are considered the most relevant to South African actors at the interface between research and policy-making, and are elaborated upon in the paper: 1. South Africa's government needs to increase expenditure on research and development to the same level as in other middle-income and BRICS countries. 2. Government officials and researchers in South Africa need to engage in co-creation of research; positive examples exist for this already. 3. Research institutions need to offer training for researchers and policy-makers. 4. Research institutions, such as South Africa's National Research Foundation (NRF) should incentivise network creation for junior researchers. 5. South African government and research institutions should strengthen “knowledge-broker” positions. The recommendations and suggestions are meant to serve as stimuli for a discussion around possible starting points for South African and international actors – Germany being the example explored here – who want to strengthen the already existing science–policy interface in South Africa.
Keywords: 330; Wissenskooperation; Aufstrebende Mächte